(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The effect of aqueous extract of Basella alba (puishak) leaves on blood cell count of rats was studied. Forty rats of both sexes weighing between 100-150 gm were used. The rats were divided into four groups (7 rats in each group), with group A as the control group and experimental groups were denoted as B, C and D. With all aseptic precautions, aqueous extract of Basella alba (Puishak) leaves was administered into the three different doses (For group B: 60 mg/kg bw, group C: 80 mg/kg bw and group D: 100 mg/kg bw). Control group A also received distilled water as a placebo at the dose of 10 mg/kg bw for 14 days. At day 15, blood samples were collected and sent for haematological analysis. Data analysis of blood count profile of 28 rats revealed that there is an increased number of RBC, WBC and platelet count in experimental groups than in control group. ANOVA test revealed that increased blood cell counts following administration of aqueous leaves extract of keeves of B. alba were statistically significant (p value for each case was .0001<.05) than control group. Paired samples t test was performed to compare between baseline hematological parameters and parameters after 14 days of intervention. Then comparison between Group A & Group B, between Group A & Group C and between Group A & Group D were done. In all cases, probability (p) value < 0.05 was considered as statistically significant.This it is clearly evident that aqueous extract of B.alba has positive stimulant effect on blood cells count of rats. Moreover, it was found that increment of doses also increases the cell count that is positively correlated with the hypothesis. Bangladesh Pharmaceutical Journal 22(1): 73-78, 2019